Biophysical measurement strategies for antiviral drug development: recent progress in virus-mimetic platforms down to the single particle level - Park, Soohyun (2022)
The rapid growth in the global human population has increased the prevalence of emerging infectious diseases, which poses a major risk to public health. In search of effective clinical solutions, the acquisition of knowledge and understanding of biomolecular processes associated with viral pathogens represents a prerequisite. In this context, biophysical engineering approaches are particularly promising since they can resolve biomolecular interactions systematically by circumventing the complexities associated with experiments involving natural biological systems. The engineering approaches encompass the design and construction of biomimetic platforms that simulate the physiological system. This approach enables us to characterize, measure, and quantitatively analyze biomolecular interactions.In this Account, we summarize biophysical measurements that our group has successfully adopted to develop broad-spectrum antiviral drugs based on the lipid envelope antiviral disruption (LEAD) strategy, targeting the structural integrity of the outer viral membrane to abrogate viral infectivity. We particularly focus on the engineering aspects related to the design and construction of the tethered lipid vesicle platform, which closely mimics the viral membrane. We first outline the development of the LEAD agents screening platform that integrates soft matter design components with biomaterials and surface functionalization strategies to facilitate parallel measurements tracking peptide-induced destabilization of nanoscale, virus-mimicking vesicles with tunable size and composition. Then, we describe how this platform can be effectively employed to gain insights into the membrane curvature dependency of certain peptides. The fundamental knowledge acquired through this systematic process is crucial in the identification and subsequent development of antiviral drug candidates. In particular, we highlight the development of curvature-sensitive α-helical (AH) peptides as a broad-spectrum antiviral agent that has been demonstrated as an effective therapeutic treatment against multiple enveloped viruses. Also, we introduce a tethered cluster of vesicles to mimic clusters of enveloped viruses, exhibiting higher infectivity levels in the biological system. Then, we discuss key considerations, including experimental artifacts, namely dye leakage and imaging-related photobleaching, and corresponding corrective measures to improve the accuracy of quantitative interpretation. With the ongoing development and application of the tethered lipid vesicle platform, there is a compelling opportunity to explore fundamental biointerfacial science and develop a new class of broad-spectrum antiviral agents to prepare for the future membrane-enveloped viral pandemics.